Cybersecurity Maturity Assessment of Jakarta Smart City Public Service Infrastructure Using NIST CSF 2.0 - Pratama, Daffa Aryasatya; Fahlevvi, Mohammad Rezza; Wulan, Puspa Ira Dewi Candra (Jurnal Studi Pemerintahan, 2026)
Digital transformation is driving local governments to develop Smart City ecosystems to enhance public service efficiency and institutional accountability. Cybersecurity vulnerabilities in Jakarta’s governance have manifestly materialised through a series of incidents that undermine public trust in government digital services, including a 2023 breach of the JAKI application, a 2024 web defacement of the official DKI Jakarta portal, an 81 GB document leak in May 2025, and the 2024 ransomware attack on the National Data Centre that disrupted 282 government agencies. This study pursues two primary objectives: to assess the cybersecurity maturity level of Jakarta Smart City (JSC) based on the NIST Cybersecurity Framework (CSF) 2.0, and to examine its implications for advancing the Sustainable Development Goals (SDGs), particularly SDG 16 (Strong Institutions), SDG 9 (Resilient Infrastructure), and SDG 11 (Sustainable Cities). The study employs a descriptive qualitative case study design, with data collected through observation, in-depth interviews, and documentary analysis conducted at the Department of Communication, Information, and Statistics of DKI Jakarta Province between December 2025 and January 2026. Maturity was assessed across 22 controls spanning the six core NIST CSF 2.0 functionsGovern, Identify, Protect, Detect, Respond, and Recoverusing the Capability Maturity Model Integration (CMMI) scoring approach. The findings place Jakarta Smart City at an overall CMMI average of 3.13, within Tier 3 (Repeatable), indicating that cybersecurity policies and controls are formally documented and consistently applied. Protect scored highest at 3.60, driven by mature IAM and infrastructure resilience, while Identify and Detect scored lowest at 3.00, primarily due to the absence of explicit data flow mapping. The study concludes that advancing cybersecurity maturity contributes significantly to reliable digital public services and public trust, thereby supporting sustainable Smart City governance aligned with SDG targets.